Gestión administrativa y su incidencia en el desempeño laboral del benemérito cuerpo de bomberos de la ciudad de Quevedo 2015 - Tigua Bejarano, Verónica Katherine (2015)
The research project entitled "Administrative management and its impact on job performance of the Distinguished Fire Brigade of the city of Quevedo," is developed in order to know how it is carrying out the administration of this public institution and is influencing this type of administration staff performance Firefighter Corps, since one way or another directly affects the citizens of our county. Within the research project the variables that comprise the research problem in order to understand where comes the research topic and objectives are detailed. In the theoretical framework we can find in detail the concepts and definitions of each of the variables containing the objectives to obtain a deeper knowledge about these. The subject of this research project chose in order to determine whether administration of this institution is influencing the work performance of employees of the fire department, because they are an organization of social assistance and should always be under the command of emergencies and in turn whether within your budget with an amount earmarked for training projects to the community This project will be very useful to the community as being a social entity helps both its administrative area as the rest of the staff should work in perfect order.